Numerical modeling of combined effects of upward and downward propagation of shear bands on stability of slopes with sensitive clay. (18th March 2016) - Dey, R.; Hawlader, B.; Phillips, R.; Soga, K.
Summary: Modeling of progressive development of zones of large inelastic shear deformation (shear band) that results from strain‐softening behavior of sensitive clays could explain the failure mechanisms of large landslides. Because of toe erosion, a shear band can be initiated and propagated upward (inward) from the river bank. On the other hand, upslope surcharge loading could generate shear bands that might propagate down towards the river bank. In the present study, upward and downward propagation of shear bands and failure of sensitive clay slopes are modeled using the Coupled Eulerian Lagrangian approach in Abaqus finite element (FE) software. It is shown that the formation and propagation of shear bands are significantly influenced by kinematic constraints that change with displacements of the soil masses, and therefore the propagation of an existing shear band might be stopped and new shear bands could be formed. The main advantages of the present FE modeling are: (i) extremely large strains in the shear bands can be successfully simulated without numerical issues, (ii) a priori definition of shearing zones is not required to tackle severe strains; instead, the FE program automatically identifies the critical locations for shear band formation and propagation. Toe erosion could significantly increase the slope failure potential because of upslope surcharge loading. FE analyses with a thick and thin sensitive clay layers show that the global failure could occur at lower surcharge loads in the former as compared to the latter cases. Copyright © 2016 John Wiley & Sons, Ltd.